Evaluación De La Calidad De Las Aguas De Los Diques Turísticos En La Subcuenca Del Río Puyo, Mediante El Uso Del Icatest V1.0. - Darwin Javier Sucoshañay Villalba; Ricardo Vinicio Abril Saltos; Leo Maximiliano Rodríguez Badillo; Fabricio Antonio Rios Rodríguez; Patricia Abigail Armas Chugcho (European Scientific Journal, ESJ, 2017)
One of the main economic centers in the province of Pastaza is the spas known as "dams." They serve as homes to a significant number of national and international tourists. Six of the province's eight dykes are located within the Puyo river basin. It was built in the upper - middle part of the basin, and is the most visited area located in the main rivers. The drawbacks of this study to ensure the quality of waters for the recreational activity are in direct contact. This can be done by using the ICOMO index (index of contamination by organic matter) to evaluate the quality of the water and to verify their status for the realization for recreational activity. Out of all the seven spas sampled, four were found to have low levels of contamination, while the remaining three had no contamination. The leaves that should be given the most attention are: Dique de Fátima and Shell. They are located in the main stream and main tributary of the study area, which exceed the permissible values in the Ecuadorian legislation in the total coliform parameter.